Penggunaan Media Literasi Digital Berbantuan Flipbook dalam Pembelajaran Daring - Emas Marlina; Rina Andriani (LPPM UNINUS, 2021)
Online learning is the choice of educational services during the pandemic. The purpose of this community service is to design, create and implement learning media using digital literacy media assisted by flipbooks in online learning. The implementation method is carried out in three stages: initial, core, and final. The results show that children have a high interest in learning activities and have a curious attitude towards the material presented. Student responses about the use of digital literacy media are that 95% enjoy learning by using flipbook-assisted digital literacy media and 5% do not enjoy it. Students' responses to the content in the material presented in the flipbook were 80% very satisfied, 15% satisfied, and 5% dissatisfied. The conclusion states that online learning with digital literacy media assisted by flipbooks can be used as an alternative to online learning.